APPLICATION OF AN OPEN MATHEMATICAL PROBLEM-ORIENTED PROBLEM-BASED LEARNING MODEL IN INFLUENCING PROBLEM-SOLVING ABILITY AND MATHEMATICAL DISPOSITION - Laksmiyeny, Desak Ayu Ike; Sariyasa, Sariyasa; Ardana, I Made (Universitas Muhammadiyah Makassar, 2024)
The improvement in students’ problem-solving ability and mathematical disposition is a highlight, especially in geometry transformation materials. This is because the learning model still uses conventional methods that emphasize students following and waiting for the direction of the teacher. This study aimed to analyze the effectiveness of problem-based learning models oriented toward open mathematical problems on the problem-solving ability and mathematical disposition of students in SMA Negeri 1 Susut. A pseudoexperimental study with a posttest-only control group design was conducted by comparing the provision of PBL and conventional learning models. The instruments used are tests and questionnaires. There are 5 items and 25 statements that meet the criteria of very high reliability. Data collection techniques in this study used test and questionnaire methods. The sample consisted of 60 students, 30 each as a control and an experiment. Data were collected using questionnaires and analyzed using MANOVA (p<0.05). The results indicate that the application of PBL models oriented towards open mathematical problems is significantly more effective than conventional learning models in improving students' problem-solving abilities and mathematical dispositions both partially and simultaneously. The application of this learning model has led to an increase in perseverance, interest, and curiosity, which are essential for problem-solving with teachers as facilitators